Variations in community sentiment toward affirmative consent policies - Miller, Monica (Criminal justice studies, 2021)
University affirmative consent (AC) policies indicate that potential sexual partners must give a clear ‘yes,’ confirming that they wish to engage in sexual activity. A lack of resistance or a failure to say ‘no’ is not enough to convey consent. These policies are critically important to both men and women, as they convey whether a student has committed a crime; yet, little is known about sentiment toward such policies. In general, understanding community sentiment is important to ensure that legal actions have the support (and ultimately, compliance) of the people who must obey them. This study investigated the support of two communities: students who are directly affected by AC polices, and community members who are not. Participants indicated their support for affirmative consent policies, beliefs about the effectiveness of affirmative consent policies, and beliefs about whether they themselves or college students would be able to comply with the policies. Sentiment toward affirmative consent polices was high (positive), although agreement that college students would be able to follow these policies was lower. Further, there was variation in sentiment, with females and students having more positive sentiment compared to males and community members. Implications for policymakers and education about AC policies are offered.